An optimal RF shielding method for MR‐PET fusion system with insertable PET. Issue 3 (September 2014) - Oh, Changheun; Han, Yeji; Kim, Dongchan; Lim, Hyunkeong; Choi, Yong; Cho, Gyuseong; Park, HyunWook
ABSTRACT An RF shielding method is proposed to preserve the resonance frequency of an RF coil regardless of the existence of a positron emission tomography (PET) detector module, so that the RF coil can effectively operate for both simultaneous MR‐PET imaging and MR stand‐alone imaging. The RF shield between the RF coil and the PET detector module was manufactured in the form of a hollow acryl cylinder wrapped with gold‐taffeta woven tape. As we adopted a double‐layer RF shield between the RF coil and the PET detector module, it was possible to maintain the resonance frequency of the RF coil and the MR image quality was similar in both cases, with and without the insertable PET detector module. Using the insertable concept of the PET system and the RF coil with an additional double‐layer RF shield, both an MR‐PET fusion system and an MR stand‐alone system were realized. © 2014 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 24, 263–269, 2014